Technical monitoring and application of swimming competition - Zhou, J.; Ba, H.; Xie, W. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: At present, Swimming on the technical and tactical basic methods of analysis used to analyze the above water video and conduct mainly some sub-timing and technical and tactical statisticsbased in the international arena. METHODS: on-site data collection and analysis are mostly used for technical and tactical statistics of the video analysis in the major international swimming events (see reference [1-8]). However, this statistical analysis is not enough and complete from the perspective of biomechanics (see reference [6]). Its main limitation is that it cannot provide technical details of technical analysis acquiring athletes in the race to use. But details of these technologies can provide a scientific basis for improving the swimming skills of athletes. Therefore, we study a test method that will be more comprehensive and complete analysis of competition. RESULTS: Our study a test method is easy to install and use software and hardware equipment under the conditions of the competition and training to complete the critical section of the above and under water camera technology. It can further analysis the key technology of players in addition to statistical analysis of video. The video acquisition and analysis system for technical analysis include (see Figure 1) a surface camera, underwater camera, image synthesis, video-signal switcher, video recorders, computers and analysis software in this study. It was applied in March 2006 Asian Swimming Championships in Singapore. DISCUSSION: Described in this article are used in swimming competition of real-time video capture, and further kinematic analysis of swimming technique video collection and analysis methods. It can get a variety of swimming skills for two-dimensional kinematic data. The accuracy of the data depends on the image quality, calibration methods and accuracy.Practical application shows that these data can basically meet the needs of the present technical analysis of swimming. This test method required fewer operations staff and equipment to the above in the application used in the test system. They have:(1) a more comprehensive measurement and feedback parameters. (2) Installation of a simple, time-saving. (3) its small size, light weight, easy to carry, easy to operate.(4) Low-voltage DC battery-powered, Security is good. (5) low cost, suitable for all kinds of swimming pools, especially those that do not use the swimming pool underwater observation equipment.